Short Communication: Candida sp. isolated from mangrove soils for biological decolorization of textile reactive dyes - PARIMA BOONTANOM; AIYA CHANTARASIRI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Boontanom P, Chantarasiri A. 2024. Short communication: Candida sp. isolated from mangrove soils for biological decolorization of textile reactive dyes. Biodiversitas 25: 2595-2602. Effluent discharge from dye-related industries is a significant environmental pollution problem and a concern for human health. Dyes have harmful effects on aquatic organisms due to their toxic properties. One possible solution is using microorganisms for the biological decolorization of textile reactive dyes as an eco-friendly and potentially lucrative alternative to physicochemical processes. Therefore, this study isolated an effective dye-decolorizing yeast from mangrove soil samples in Thailand and investigated the decolorization efficiency of eight textile reactive dyes under experimental conditions. Yeasts have several advantages over other bacteria and fungi for the biological decolorization of textile reactive dyes, but the number of dye-decolorizing yeasts discovered in mangrove soils remains scarce. The most effective dye-decolorizing yeast, isolate RY21703, showed Remazol Brilliant Blue R (RBBR) decolorization of 37.50±0.07% within 72 h of incubation. This yeast isolate was genetically and phylogenetically identified as Candida sp. strain RY21703 and produced 0.97±0.08 U/mL of crude laccase activity, an essential enzyme in dye decolorization mechanisms. Candida sp. strain RY21703 showed strong decolorization efficiency after 72 h of incubation in all azo-reactive dyes, ranging from 27.32±3.34% (CI Reactive Orange 122) to 61.45±1.43% (CI Reactive Green 19). This strain also decolorized phthalocyanine reactive dye (CI Reactive Blue 21) by 60.71%. Findings suggested that this mangrove yeast can be used for the biological decolorization of dyeing wastewater.